MENTAL PERFORMANCE IN NOISE: THE ROLE OF INTROVERSION - BELOJEVIC, G.; SLEPCEVIC, V.; JAKOVLJEVIC, B. (Journal of environmental psychology, 2001)
A mental arithmetic task was applied on 123 medical students (43 males and 80 females) under quiet (42 dB/A/Leq) and noisy laboratory conditions (recorded traffic noise, 88 dB/A/Leq). Personality trait of intro-extroversion was estimated with the Eysenck Personality Questionnaire. Two groups of subjects were formed concerning intro-extroversion, using a testing mean score as a dividing criterion: 46 introverts (<mean score) and 77 extroverts (>mean score). Concentration problems, fatigue and noise annoyance during the experiments were measured with numeric ten-point self-rating scales. There was no significant effect of noise on the accuracy of mental processing, compared to the quiet condition. Extroverted subjects performed significantly faster in noise, compared to the quiet condition (p<0·05). Concentration problems and fatigue were more pronounced in noise, compared to quiet conditions, but that was only among introverted subjects (p<0·05). Correlation analysis revealed a highly significant negative relation of extroversion and noise annoyance during mental processing (p<0·01).